Faktor – Faktor Yang Mempengaruhi Produktivitas Karyawan Bappeda Kabupaten Jepara: Insentif, Disiplin Kerja dan Motivasi Kerja - Amalia, Zulfa Khasna; Oktavia, Vicky (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to study how incentives, work discipline, and work motivation impact employee productivity at the Jepara Regency Regional Planning, Development, Research, and Development Agency. This study uses multiple linear analysis as a quantitative methodology. Validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression, F test, t test, and coefficient of determination tests were conducted. using questionnaire data distributed to 62 employees, and collecting valid data from 62 respondents. The census sampling method was applied for sampling. The results of the analysis using SPSS showed that the incentive and work motivation variables had a positive and significant effect on employee productivity. On the other hand, the work discipline variable did not show a significant effect on employee productivity, but tended to be negative.